The definition of the direction of forces arising during the interworking of a car’s steer wheel with chassis dynamometer - Vasyliev, Oleksiy; Rohozin, Ivan; Shapoval, Mykola; Orysenko, Oleksandr (Academic journal Industrial Machine Building Civil Engineering, 2018)
The article gives the theoretical substantiation of the forces determination that arise during the steerable vehicle wheel with chassis dynamometer interaction taking into account the wheels angles setting in relation to the longitudinal, vertical and transverse vehicle axes. The transition from mobile to fixed coordinate system using Euler angles is considered. The transitions comparison from the stationary coordinate system to the moving one in the system an aircraft axes and ship axes. It made it possible to move to the fixed coordinate system for a steerable vehicle wheel. A table of transition between moving and stationary reference systems has been made. The table provides an opportunity to determine the projections of forces that arise when the steerable vehicle wheel is interacting with the bearing surface when the angles of its installation are relative to the frame, are changed.